A corpus-based study of time metaphors in the text simplification of ‘Around the World in 80 Days’ / Noor Baizura binti Adnan @ Anang - Adnan @ Anang, Noor Baizura (2014)
Corpus-based method is increasingly applied in the investigation of conceptual metaphors. Automatic semantic domain identification of target domain and source domain required when forming metaphors can now be carried out quite satisfactorily. In this study, the semantic domain tagger UCREL Semantic Analysis System (USAS) was used to explore the conceptualization of time in the novel ‘Around the World in 80 Days’ and its simplified version. Specifically, it is an investigation on how the concept of time is changed in a simplified text. First, semantic domains were extracted and then followed by a manual identification of metaphorical expressions using the Conceptual Metaphor Theory (Lakoff & Johnson, 1980). Next, the metaphor of TIME was classified according to its types to detect any gain or loss of metaphors after the text is simplified. Finally, the patterns of changes of metaphors in simplified literary texts were explored using the framework proposed by Deignan, Littlemore & Semino (2013). The results showed that USAS may be used for identification of semantic domains which is an important step in extracting metaphorical expressions from the texts. Two out of nine types of TIME metaphor initially found in the original text disappeared in its simplified version, i.e. personification and TIME IS DISTANCE metaphors. The patterns of changes of metaphors where the metaphors were added, removed, retained and altered provide an insightful perception on changes that occurred and the rationales of those changes when a text is simplified. The usability of a corpus tool in extracting the semantic domain of time in detecting metaphorical expressions has confirmed the potential of corpus-based methodology in analyzing conceptual metaphors. The combination of corpus-based method and cognitive metaphor theory provides an empirical support for the observation of the distribution of time metaphor in literary texts suggesting that the application of corpus-based method can provide versatility in linguistic analysis.